Emerging Between Two Worlds: A Longitudinal Study of Career Identity of Students From Asian American Immigrant Families. Issue 1 (February 2018) - Polenova, Elena; Vedral, Amie; Brisson, Leanna; Zinn, Leanne
This study examines career identity formation of Asian American college students from first-generation immigrant families as a model of acculturation. The interaction between collectivist and individualistic values was explored through analysis of longitudinal interview data. The semistructured interviews were conducted with 12 participants across 4 years of college. We utilized a hybrid deductive–inductive approach for thematic analysis of interviews and matrices to visualize longitudinal trajectories. Factors impacting career identity development were family influence—including cultural values, parental pressure, cultural capital and family obligation, and individual characteristics—including identity style, locus of control, and personal motivation. Longitudinal development proceeded along four trajectories: continual foreclosure, moratorium to achievement, foreclosure to achievement, and continual diffusion. Our results indicate that career identity development for Asian American college students is characterized by the interaction between two cultures and individual characteristics. Implications for counseling and higher education are discussed.